Association of Pesticide Use and Personal Protective Equipments with Health Complaints among Horticulture Farmers in Buleleng, Bali - Ida Ayu Dwi Astuti Minaka; Anak Agung Sagung Sawitri; Dewa Nyoman Wirawan (Universitas Udayana, 2016)
Background and purpose: Uses of highly toxic pesticides mostly occur in developing countries, including Indonesia. Farmers at Pancasari village in Bali were active pesticide users, that potential for pesticide poisoning. Pesticides and personal protective equipment (PPE) use and their relationship with health complaints on farmers in that region are not well known. Methods: Cross sectional survey was conducted among 87 horticultural farmers. Univariate, bivariate (chi square test) and multivariate (using logistic regression) analysis were conducted to understand relationship between health complaints related to pesticides used (at least two health complaints of: headache, itching, fatigue and nausea) with socio-demographics, knowledge and use of pesticides and PPE behaviour. Results: The majority (94.3%) of farmers aged less than 30 years and 81.6% were male with secondary education or lower (78.2%). More than half (54.1%) farmers had moderate knowledge about pesticides and PPE, however they had poor behaviour. A total of 60.9% farmers experienced specific health complaints. Health complaints were associated with use of organophosphate (AOR=3.74; 95%CI: 1.33- 10.48), number of days use of work clothes before being washed (AOR=1.37; 95%CI: 1.08-1.75), not wearing long-sleeve clothes when mixing pesticide (AOR=0.25; 95%CI: 0.09-0.76) and not wearing a mask when spraying pesticide (AOR=0.18; 95%CI: 0.05-0.69). Conclusion: Health complaints were associated with type of organophosfat pesticide, behavior of work clothes used before being washed and inadequate use of personal protective equipments.